Using research networks to generate trustworthy qualitative public health research findings from multiple contexts - Nyirenda, Lot; Kumar, Meghan Bruce; Theobald, Sally; Sarker, Malabika; Simwinga, Musonda; Kumwenda, Moses; Johnson, Cheryl; Hatzold, Karin; Corbett, Elizabeth L.; Sibanda, Euphemia; Taegtmeyer, Miriam (BMC medical research methodology, 2020)
Qualitative research networks (QRNs) bring together researchers from diverse contexts working on multi-country studies. The networks may themselves form a consortium or may contribute to a wider research agenda within a consortium with colleagues from other disciplines. The purpose of a QRN is to ensure robust methods and processes that enable comparisons across contexts. Under the Self-Testing Africa (STAR) initiative and the REACHOUT project on community health systems, QRNs were established, bringing together researchers across countries to coordinate multi-country qualitative research and to ensure robust methods and processes allowing comparisons across contexts. QRNs face both practical challenges in facilitating this iterative exchange process across sites and conceptual challenges interpreting findings between contexts. This paper distils key lessons and reflections from both QRN experiences on how to conduct trustworthy qualitative research across different contexts with examples from Bangladesh, Ethiopia, Kenya, Indonesia, Malawi, Mozambique, Zambia and Zimbabwe.
Gesehen am 04.05.2020